Nontuberculous mycobacteria in clinical samples with negative acid-fast bacilli - Alejandro Hernandez-Solís; Raúl Cicero-Sabido; Maribel González-Villa; Isaura Isabel Martínez-Rivera; América del Pilar Mandujano-Martínez; Benita Pilar Torres-Mazadiego; Claudia Elena Wong-Arámbula; Abril Paulina Rodríguez-Maldonado; Lucia Hernández-Rivas; Heleodora González-González; José Ernesto Ramírez-González (International Journal of Mycobacteriology, 2017)
Background: There is a progressive increase in nontuberculous mycobacteria (NTM) in pulmonary and extrapulmonary infections that might cause confusion with the Mycobacterium tuberculosis complex. To determine the frequency of finding NTM in clinical samples from patients diagnosed with active tuberculosis, with negative acid-alcohol-resistant bacilli (acid-fast bacillus [AFB]) in a third-level specialty hospital's mycobacterial laboratory between January 2013 and December 2014. Methods: This is a prospective, descriptive study where isolated strains of biological material were studied in Lowenstein–Jensen and BACTEC MGIT 960 cultures. Results: Clinical samples of 120 patients were studied, with pulmonary samples of 99/120 (82%) and extrapulmonary samples of 21/120 (18%). We identified NTM in 37/120 samples (30.8%), of which 16 in pulmonary, 13 in genitourinary, 3 in bone marrow, and 5 in various specimens. Mycobacterium avium was isolated in 20 samples, Mycobacterium intracellulare in seven samples, and various other species of NTM in the other 10 samples. Conclusion: To establish adequate treatment, we point out the importance of identifying the presence of NTM in the clinical samples of active tuberculosis patients with negative AFB, as possibly becoming confused with M. tuberculosis and which is essential in deciding which treatment is the most adequate.